PENGGUNAAN INSTRUMEN PENGAMANAN PERDAGANGAN INTERNASIONAL DAN STRATEGI PERSAINGAN GLOBAL - Murti, Hari; Pramesi, Mutiah (Jurnal Ilmu Ekonomi dan Pembangunan, 2006)
Free and trade as basic principles of GATT/WTO (General Agreement on Tariffs and Trade/World Trade Organization) do not fully benefit to its member countries. Thought GATT/WTO rules consist of agreements believed to lower down trade barriers (tariffs and non-tariffs) among member countries, with their main key of helping trade to flow smoothly by giving equally Most Favored-Nation Treatment (MFN-Status), non discriminating amongst trading partner, and binding tariff rates as well as market opening commitment in WTO. GATT/WTO rules are agreements regulating to came down trade barriers among country member and directing for fair and transparent trade internationally, thought GATT/WTO rules also permit to give escape clause for member countries to waive basic principles of WTO within certain period of time, inter safeguards, in additional to antidumping and subsidy. The rules constitute contigent trade protection against free imports in to country members within any barriers.?Keywords : free and fair trade, agreements regulating, safeguards, dumping and subsidy.??????? ?